Integrating cancer patients' perspectives into treatment decisions and treatment evaluation using patient‐reported outcomes – a concept paper. (25th July 2013) - Huebner, J.; Rosé, C.; Geissler, J.; Gleiter, C.H.; Prott, F.J.; Muenstedt, K.; Micke, O.; Muecke, R.; Buentzel, J.; Bottomley, A.; Hofheinz, R.‐D.
<x xml:space="preserve">Abstract</x> Patient‐reported outcomes are an important tool in clinical research. In the setting of cancer treatments, benefit of therapy is essentially characterised by improvement of survival as well as quality of life (QoL). A standardised instrument to assess QoL is the standardised QoL questionnaire of the European Organisation for Research and Treatment (EORTC QLQ‐C30 questionnaire). QoL instruments provide data on different aspects (domains) of the framework of QoL. Using these questionnaires in studies provides data on how a treatment affects QoL in a group of patients. The goal of our concept is to individualise QoL and to use validated instruments in order to integrate patients' perspectives and aims into treatment assessment, planning and control. We propose to use the domains of the EORTC QLQ‐C30 and to ask the patient to determine which objectives besides survival are relevant for him and should be achieved by treatment. These individual goals can be used in a process of shared decision‐making to choose and monitor treatment. In clinical studies, this approach would allow to recruit more patients who would most probably benefit from the therapy. In addition, supportive data could be gathered in correlation to treatment goals and actual benefits.